A urbanização do território no Rio Grande do Norte - Santos, Elizabete Rodrigues Gurgel dos (2021)
Urbanization is an ancient process of humanity and one of the most discussed themes in Geography. However, the works that have discussed urbanization as a process that form cities and the rural and the urban as excluding are still frequent, thus reproducing some dichotomies that make it impossible to understand space as a totality. This dichotomous rural-urban conception generates territorial repercussions when considering the theoretical-methodological conceptions adopted by institutions and firms that work with planning. It is assumed that the urbanization of a certain portion of the territory is directly related to the uses and techniques that exist in it and, in this sense, when analyzing the reality of Rio Grande do Norte empirically, a rarefaction of urbanization in many areas. In addition, a process of capillarization of urban content throughout the territory is notorious, both in the countryside and in the city, but at different levels. The municipal government has attributed to the municipalities of Rio Grande do Norte a higher level of urbanization than they actually have, and in some cases has ignored the coexistence of rural content. The acceptance of a higher level of urbanization than the state actually presents, has served as a strategy to increase the profitability of the real estate sector. And, it has caused the land to become more expensive in different areas, the exclusion of rural workers from economic and social policies, and the precarious insertion in the territory of a considerable part of the population of Rio Grande do Norte. From this perspective, the general objective of this research is to analyze the different technical levels of urbanization of the territory in Rio Grande do Norte, considering the rural-urban complementarity, and the territorial repercussions of considering different areas of the same with a greater urbanization density than that they actually present. For this, an urbanization index was created based on the indicative elements of urbanization to measure its different technical levels. Field and documentary research, analysis of primary and secondary data and spatial descriptive analysis with classification of satellite images were also carried out, in order to identify the evolution of urbanization in Rio Grande do Norte over three pre-selected periods, as well as intra-municipal differences. With this, it can be seen that, despite the urban content having spread throughout the territory of Rio Grande do Norte, especially from the emergence of the technical scientific informational environment, which has been effective in the State, in fact, from the 1990s onwards, a large part of the municipalities of Rio Grande do Norte still present low technical density, and therefore, a rarefaction of urban content. This fact reveals that just classifying the parcels of territory into rural and urban are not enough for purposes of planning and management of the territory, it is necessary to assess the density of this urbanization to think about social and territorial policies that contribute to the promotion of social justice, development and to alleviate the great abyss resulting from the accentuated social inequality historically reproduced and neglected by the public policies implemented in the state.